2018
DOI: 10.1080/2162402x.2018.1438109
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 (HMGB1) acts as an “alarmin” to promote acute myeloid leukaemia progression

Abstract: High mobility group box 1 (HMGB1) is a non-histone protein localised in the cell nucleus, where it interacts with DNA and promotes nuclear transcription events. HMGB1 levels are elevated during acute myeloid leukaemia (AML) progression followed by participation of this protein in triggering signalling events in target cells as a pro-inflammatory stimulus. This mechanism was hypothesised to be employed as a survival pathway by malignant blood cells and our aims were therefore to test this hypothesis experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Importantly, stress associated with the events described above leads to release of HMGB1 (high-mobility group box 1) protein by AML cells, which ultimately triggers the production of IL-1β by healthy leukocytes. 14 has been reported to induce the expression and production of stem cell factor (SCF) by epithelial cells via the mTOR pathway and hypoxic signaling. 15 SCF is a major hematopoietic growth factor that controls AML progression, thus becoming highly oncogenic.…”
Section: T Helpers and Ctcs/nk Cells Express Pd-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, stress associated with the events described above leads to release of HMGB1 (high-mobility group box 1) protein by AML cells, which ultimately triggers the production of IL-1β by healthy leukocytes. 14 has been reported to induce the expression and production of stem cell factor (SCF) by epithelial cells via the mTOR pathway and hypoxic signaling. 15 SCF is a major hematopoietic growth factor that controls AML progression, thus becoming highly oncogenic.…”
Section: T Helpers and Ctcs/nk Cells Express Pd-1mentioning
confidence: 99%
“…15 In this way, AML cells employ body systems to produce factors required for their proliferation/ disease progression. 14,15 Taking these results together, it is clear that AML cells implement comprehensive mechanisms to escape immune surveillance and facilitate disease progression. Pharmacological targeting of the biochemical pathways responsible for immune escape will enable the human immune system to potentially cure AML, with the goal of avoiding aggressive chemotherapy and bone marrow transplantation.…”
Section: T Helpers and Ctcs/nk Cells Express Pd-1mentioning
confidence: 99%
“…This indirect effect occurs via Hmgb1, which we show to be elaborated downstream of Ifnγ. Hmgb1 is a non-histone chromatin binding protein and a member of the alarmin family (43,44). It is known to function as a mediator of inflammatory processes by binding to its receptors including RAGE and a subset of TLRs (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of cellular signaling pathways have been identified that contribute to T-bet induced differentiation of Th1 in patients with CVD, and their targeting could provide a new therapeutic strategy in patients (Table 2) to the secretion of VEGF by macrophages and neutrophils Soloviev et al, 2014). It has also been shown that HMGB-1 factor leads to the release of both TNF-α and VEGF; therefore, HMGB-1 is likely to stimulate angiogenesis via TNF-α mediation (Yasinska et al, 2018).…”
Section: The Role Of T-bet In Cvd Angiogenesismentioning
confidence: 99%